Case study on a fire within a road‐based portable bitumen storage tanker. Issue 4 (1st February 2019) - Pittman, William; Mannan, M. Sam
Abstract : The roofing industry makes use of bitumen to build and repair roofs of residential and commercial structures. It is therefore necessary to transport the material over roadways and into residential and light commercial areas within cities. This is oftentimes accomplished by hauling the material behind trucks in large tankers that often have capacities of a few thousand gal. The material is flammable however and emits toxic and flammable off‐gases as it ages. As such, the storage, handling, transportation, and use of this material is inherently hazardous and these road portable tankers present a hazard not only to the companies and employees that use them, but also to the communities and businesses the companies serve. This article examines the events leading up to a fire that began within one such towed bitumen storage tanker used by a roofing company in Montreal in 2009. The incident is reviewed along with the hazards posed by these tankers. Conclusions are presented with regard to the causation of the fire based on the design of the tanker and available information. The learnings from this incident may prove helpful to other businesses that process, store, and use high molecular weight, sulfur‐containing hydrocarbon mixtures. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12038 2019